Case study on BIM for Box Culvert design in infrastructure modeling and quantity estimation (2024)
Building Information Modelling (BIM) has been cataloged as a revolutionary methodology that has changed the way buildings and infrastructure are designed, constructed, and managed. While in different countries it has been widely implemented for infrastructure projects, it has fallen short in the AEC industry in Colombia. This paper delves into the application of BIM methodology focusing on hydraulic design through a case study of a Box Culvert using Revit. The BIM tool for quantity estimation was measured both quantitatively and qualitatively in comparison to traditional methodology. The research unveils the positive aspects of BIM, including the cost/time savings of parametric families. Contrarily, Revit as BIM software fails to go through, as primarily designed for building modeling, lacking the specific requirements for infrastructure projects. Due to the positive results, it is advised for companies to invest strategically, recognizing initial costs as essential for long-term efficiency gains.